Makna simbolis Srimpi Lima pada upacara Ruwatan di Desa Ngadireso Poncokusumo Malang - Harini, Ninik (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
In Ngadireso, Poncokusumo, Malang, the Srimpi Lima dance is performed by five dancers wearing similar costumes but different colors of sampur. The floor pattern is rectangular, allowing clockwise movement by the dancers. Moreover, this dance has symbolic meaning due to its function as a ruwatan ceremony for ontang-anting, or an only child who is considered a sukerta child. The aim of this study is not only to describe the performance and function but also the symbolic meaning of the Srimpi Lima dance in the ruwatan ceremony. To obtain a clear description, the researcher applied a qualitative descriptive method through interviews, observation, documentation, and document collection. The research procedure was conducted through several stages: planning, conducting the research, data analysis, and data presentation. The results of the study show that the symbolic meaning of the Srimpi Lima dance is intended to purify the sukerta child.